Anomalous lattice expansion of RuSr2Eu1.5Ce0.5Cu2 O10-δ (Ru-1222) magneto superconductor: A low temperature X-ray diffraction study - Awana V.P.S.; Ranjan R.; Rawat R.; Chandra L.S.S.; Peurla M.; Ganesan V.; Kishan H.; Pandey D.; Laiho R.; Takayama-Muromachi E.; Narlikar A.V. (My University, 2025)
Detailed X-ray diffraction studies on RuSr2Eu1.5Ce0.5Cu2 O10-δ (Eu-Ru-1222) magneto superconductor down to 13 K at close temperature intervals revealed that with decreasing temperature, the c-parameter decreases linearly down to 100 K, following the relation c = 28.412(1) + 2.5(1) × 10-4T and then becomes almost temperature independent on further lowering of temperature. Interestingly, the linear decrease in the a-parameter is seen only up to 180 K. Below 180 K, the observed values of the a-parameters are more than the value expected from the linear variation. This departure can be considered as development of strain in the system. Interestingly enough, these temperatures coincide with the complex magnetic ordering (Tmag) of Ru in Ru-1222 system. This is the first report of the observation of the onset of excess volume and also of the strain along the a-axis near the magnetic ordering temperature in Ru-1222 superconductor, and indicates a coupling between the lattice and the magnetism in this system. Magnetization, magneto transport and thermoelectric power measurements being carried out on the same sample are also reported. The results of low temperature excess volume and the strain along a-axis of Ru-1222 compound are reportedly not seen in Ru-1212 (RuSr2GdCu2O8). © 2006 Elsevier B.V. All rights reserved.